Desempenho de genótipos de milho sob diferentes espaçamentos entre linhas para múltipla aptidão - Silva Júnior, Antônio Barbosa da (2015)
The experiments were conducted at the sector of Breeding Plants of the Center of the Federal University of Alagoas Agricultural Sciences (SMGP-ECSC-UFAL) in the municipality of Rio Largo-AL. Experiment 1 was conducted from December 2013 to April 2014, in the experimental area of that sector and the experiment 2 was conducted from April to June 2014, at the Laboratory of SMGP-ECSC-UFAL, in order to evaluate the performance of corn genotypes (Zea mays L.) for multiple fitness for high population density for the production of silage and grain. The experiments evaluated two treatment groups: Group 1: Genotypes of Maize and Group 2: Spacing between lines. In Group 1, were evaluated eight maize genotypes, five developed by SMGP-ECSC-UFAL: Alagoas, White, Northeast, St. Louis and Viçosense; two varieties; a developed by the Brazilian Agricultural Research Corporation (EMBRAPA): BR 106 (Foot Ox), the other by the CATI-SP (AL Bandeirante); and a variety of Creole founded average backcountry Alagoas (Jabotão). In Group 2, were evaluated two spacings: 0.6 mx 0.20 mx 0.2 m me 0.8, with 10 plants per meter, representing the population densities of 166,667 and 125,000 plants.ha-1, respectively. In Experiment 1, we used the experimental randomized block design, in factorial arrangement of 8 x 2, with three replications, totaling 48 experimental plots. Plots consisted of 4 rows of 6 m long with 2 plants per hole. The total area of the plot of 14.40 m2 for spacing of 0.60 mx 0.20 me of 19,20 m2 for the spacing of 0.8 mx 0.20 m. Each plot had three working areas, one for the production of silage, one for the production of grain and the other to the ear relationship, leaf and stem. In Experiment 2, we used the completely randomized design in a factorial 8 x 2, with three replications, totaling 48 experimental plots. Each experimental plot consisted of a PVC pipe of 0.50 m long and 0.10 m in diameter, with a volume of 0.157 m³ (Experimental Silo). Variables of agronomic interest for the production of silage and grain were evaluated. The reduction of spacing between planting rows of 0.80 to 0.60 m, with two plants / plant, and consequent increase in population density of 125,000 to 166,667 plants.ha-1, provides a higher yield of grain and green mass the whole plant, without changing other agronomic characteristics evaluated. The genotypes of SMGP-ECSC Viçosense, White and St. Louis and the variety Creole Jabotão had the highest grain yield with increasing population density of 125,000 to 166,667 plants.ha-1, over 13 tonnes per hectare. The Viçosense genotype was very responsive to increased population density of 125,000 to 166,667 plants.ha-1, with a yield around 16 tons of grain per hectare and can be recommended as a standard of responsiveness in future genetic corn breeding programs. The genotypes of the ECSC SMGP-Alagoas, White, Northeast, St. Louis and Viçosense showed an average yield of green matter of the whole plant 62940.29 kg ha-1, an average percentage of 48.00% and an average percentage spikes stalk of 34.44%, these favorable characteristics for silage. The White genotype is the most suitable for high quality silage production by a high yield of green matter of the whole plant, about 71 tonnes of dry matter per hectare high contribution spikes above 50%, and low stalk contribution, around 33%.